Thermal Residual Stress Analysis of Soldering and Lamination Processes for Fabrication of Crystalline Silicon Photovoltaic Modules - Hyunseong Shin; Ekyu Han; Nochang Park; Donghwan Kim (Energies, 2018)
In this study, we developed a finite element model to assess the residual stress in the soldering and lamination processes during the fabrication of crystalline silicon (Si) photovoltaic (PV) modules. We found that Si wafers experience maximum thermo-mechanical stress during the soldering process. Then, the Si solar cells experience pressure during the process of lamination of each layer of the PV module. Thus, it is important to decrease the residual stress during soldering of thin Si wafers. The residual stress is affected by the number of busbars, Si wafer thickness, and solder type. Firstly, as the number of busbars increases from two to twelve, the maximum principal stress increases by almost a factor of three (~100 MPa). Such a high first principal stress can cause mechanical failure in some Si wafers. Secondly, thermal warpage increases immediately after the soldering process when the thickness of the Si wafers decreases. Therefore, the number and width of the busbars should be considered in order to avoid mechanical failure. Finally, the residual stress can be reduced by using low melting point solder. The results obtained in this study can be applied to avoid mechanical failure in PV modules employing thin Si wafers.